2011
DOI: 10.1111/j.1475-6811.2011.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and depressive symptoms in middle childhood and early adolescence: Testing the validity of the emotion regulation model of attachment

Abstract: This research examines differential associations between attachment dimensions (anxiety and avoidance) and emotion regulation (ER) strategies (dysregulation and suppression) in middle childhood and early adolescence. Furthermore, the study investigates how attachment and ER relate to depressive symptoms and perceived parenting. Two cross-sectional studies (N = 339 and N = 746) supported the hypothesized associations between attachment anxiety and avoidance and emotional dysregulation and suppression, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
122
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 44 publications
11
122
0
3
Order By: Relevance
“…More avoidantly attached children are likely to refuse care from attachment figures. Instead, they try to ignore or suppress (negative) emotions (Brenning et al 2012;Brumariu 2015;Cassidy 1994). They more likely avoid situations that elicit negative emotions, but also positive emotions.…”
Section: Moderators and Mechanisms Explaining Links Between Attachmenmentioning
confidence: 99%
See 2 more Smart Citations
“…More avoidantly attached children are likely to refuse care from attachment figures. Instead, they try to ignore or suppress (negative) emotions (Brenning et al 2012;Brumariu 2015;Cassidy 1994). They more likely avoid situations that elicit negative emotions, but also positive emotions.…”
Section: Moderators and Mechanisms Explaining Links Between Attachmenmentioning
confidence: 99%
“…Moreover, they tend to heighten their negative emotional states (for example by ruminating about negative emotions or by expressing anger about the attachment figure's failure to be responsive and sensitive) to elicit care (Cassidy 1994). At the same time, any care they receive activates fear to be again disappointed by the caregiver's rejection, abandonment, or neglect (Brenning et al 2012;Cassidy 1994). This has been described as an hyperactivating emotion regulation strategy (Mikulincer and Shaver 2007).…”
Section: Moderators and Mechanisms Explaining Links Between Attachmenmentioning
confidence: 99%
See 1 more Smart Citation
“…The null findings at the actor level are consistent with previous research showing inconsistent findings between attachment anxiety and support-seeking (Alexander, Feeney, Hohaus, & Noller, 2001;Berant, Mikulincer, & Florian, 2001;Ognibene & Collins, 1998;Radecki-Bush, Farrell, & Bush, 1993). Thus, it is possible that anxiously attached individuals do not always seek support when distressed as they worry about the availability of the attachment figure due to a history of receiving unpredictable or inconsistent care and support (Ainsworth et al, 1978;Brenning et al, 2012). As previously noted, the significant partner effect was not supported at the correlational level; therefore, it is likely to be the results of a suppression effect in the multiple regression analysis.…”
Section: Discussionmentioning
confidence: 43%
“…Individuals who are high in attachment anxiety worry about their own value to the attachment figure and about the availability of the attachment figure due to a history of receiving unpredictable or inconsistent care and support (Ainsworth et al, 1978;Brenning, Soenens, Braet, & Bosmans, 2012). Research has found that individuals who are high in anxiety manage distress by using passive, ruminative, and emotion-focused coping strategies (Campbell et al, 2001;Chow & Buhrmester, 2011).…”
Section: Attachment Representations and Co-ruminationmentioning
confidence: 99%